Intrauterine drug exposure as a risk factor for cerebral palsy. (16th September 2021) - Benninger, Kristen L; Purnell, Jessica; Conroy, Sara; Jackson, Kenneth; Batterson, Nancy; Neel, Mary Lauren; Hester, Mark E; Maitre, Nathalie L
Abstract : Aim: To determine whether infants with intrauterine drug exposure (IUDE) are similarly at risk for cerebral palsy (CP) as other high‐risk populations, whether CP classification differs based on IUDE status, and describe the association of CP with specific substances among exposed infants. Method: This was a retrospective analysis of infants in a high‐risk follow‐up program ( n =5578) between January 2014 and February 2018 with a history of IUDE or who received a CP diagnosis. CP rates were compared using two‐sample z ‐tests. CP classification was assessed using Fisher's exact, Cochran–Armitage, and Wilcoxon rank‐sum tests. Models for CP risk were assessed using multivariable logistic regression. Results: Among all infants with IUDE ( n =1086), 53.8% were male with a mean (SD) birth gestational age of 36.8 (3.6) weeks. Among unexposed infants with CP ( n =259), 54.4% were male with a mean (SD) birth gestational age of 29.9 (5.7) weeks. Opioids were the most common exposure (93.7%) of all infants with IUDE. The CP rate in the IUDE (5.2%) and unexposed (5.7%) high‐risk populations were not significantly different ( p =0.168), nor were there differences in CP typology, topography, or severity between exposed ( n =57) and unexposed ( n =259) infants (all p >0.05). In patients with IUDE and after controlling for established CP risk factors, the observed odds of CP varied among substances. Interpretation: We suggest that IUDE should be considered a 'newborn‐detectable risk' in the guidelines for the early detection of CP. Abstract : This original article is commented by Gao on page 403 of this issue.